THE STRATEGIC ROLES OF HUMAN RESOURCE MANAGER TO ACHIEVE COMPETITIVE ADVANTAGE IN HOSPITALITY INDUSTRY - Suryaningtyas, Dianawati; Asna, Asna (Jurnal Aplikasi Manajemen, 2017)
The global challenges in the economic sector has become more complex and turbulence. Many companies have executed management changes in order to survive and create strategies to compete with their competitors. More than two decades, human resource management has been developed into strategic to face the global challenges, and the roles concept of human resource professional created by Ulrich et. al. has been executed by many companies around the world. Many researchers have stated that a key to achieving competitive advantage is that of the strategic roles of human resource management. In the service industry, specifically in hospitality, in which human resource as the main resource to run the business, the strategic roles of the human resource manager is very important in creating competitive advantage. This research aims to identify and describe the strategic roles of human resource managers in a hospitality industry. This study conducted in three-star hotels in Malang and interviewed six human resource managers as participants. Qualitative method used in this research and positivist underlying philosophical assumption. Using semi-structured interview in data collection, this paper identifies three themes to be analyzed by coding using software NVivo International 10. The first is the strategic roles of human resource managers contribute to anticipating the competitive business challenges; the second, their strategic roles in creating competitive advantage; and lastly, a human resource as a key in creating the competitive advantage for the company. The first two themes are analyzed by a number of coding references, the finding mentioned that there are two human resource managers who conduct strategic roles as the strategic partner and change agent. While the third theme is analyzed by word tree and giving the result that the factor of achieving competitive advantage is that of human resource.